A Comparative Analysis of Soil Loss Tolerance and Productivity of the Olive Groves in the Protected Designation of Origin(PDO) Areas Norte Alentejano (Portugal) and Estepa (Andalusia, Spain) - Rodríguez-Sousa, Antonio Alberto (2021)
Olive groves are Mediterranean systems that occupy more than 2.5 M ha in Spain and 0.352 M ha in Portugal. Assuming the differences between both countries in terms of olive grove regulation and considering their multifunctionality, it is useful to implement agronomic indices to estimate their sustainability. The Soil Loss Tolerance Index (SLTI) and the Soil Productivity Index (SPI) are two such indices. We calculated both indices in the Protected Designation of Origin (PDO) Norte Alentejano (Portugal). The SLTI index was adapted considering specific variables of the analysed olive groves (i.e., SLTIog). The values obtained were compared with those previously estimated for PDO Estepa (Spain). The negative impacts of erosion and the underlying agricultural practices on the sustainability of olive groves became evident, resulting in decreased soil productivity at the regional level. The SLTIog index showed higher values for crops, being a more realistic tool to analyse sustainability. A higher soil loss tolerance was detected for integrated groves in the PDO Norte Alentejano than for PDO Estepa due to the shorter age of olive cultivation in Portugal, with incipient soil impacts. These indices provide information on the degree of soil erosion, allowing farmers and decision-makers to apply practices to maximise the sustainability of olive groves.